2012
DOI: 10.1038/embor.2012.160
|View full text |Cite
|
Sign up to set email alerts
|

Defining a new role of GW182 in maintaining miRNA stability

Abstract: GW182 binds to Argonaute (AGO) proteins and has a central role in miRNA-mediated gene silencing. Using lentiviral shRNAinduced GW182 knockdown in HEK293 cells, this study identifies a new role of GW182 in regulating miRNA stability. Stably knocking down GW182 or its paralogue TNRC6B reduces transfected miRNA-mimic half-lives. Replenishment of GW182 family proteins, as well as one of its domain D12, significantly restores the stability of transfected miRNA-mimic. GW182 knockdown reduces miRNA secretion via secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 29 publications
0
31
0
2
Order By: Relevance
“…Indeed, a prominent feature of circulating miRNAs is their remarkable stability (51): they are protected by forming complexes with proteins such as Argonaute (52) and GW182 (53) or are encapsulated in exosomes that provide additional protection from degrading enzymes (54). Moreover, miRNAs are a specific product of the embryo that can be related to the quality of many differentiation processes that beset blastocyst differentiation and are not supposed to be already present in culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a prominent feature of circulating miRNAs is their remarkable stability (51): they are protected by forming complexes with proteins such as Argonaute (52) and GW182 (53) or are encapsulated in exosomes that provide additional protection from degrading enzymes (54). Moreover, miRNAs are a specific product of the embryo that can be related to the quality of many differentiation processes that beset blastocyst differentiation and are not supposed to be already present in culture media.…”
Section: Discussionmentioning
confidence: 99%
“…GW-bodies also contain GW182 and AGO2, proteins of the RISC complex which have also been identified in exosomes (69). Interestingly Yao et al reported that a knock-down of GW182 decreases the miRNA release via secretory exosomes (225). Furthermore, Guduric-Fuchs et al showed that a knock-out of AGO2 also reduces the incorporation of miRNAs into exosomes (72, 225).…”
Section: Transfer Of Ex-srnas Into Human Circulationmentioning
confidence: 99%
“…Interestingly Yao et al reported that a knock-down of GW182 decreases the miRNA release via secretory exosomes (225). Furthermore, Guduric-Fuchs et al showed that a knock-out of AGO2 also reduces the incorporation of miRNAs into exosomes (72, 225). Whether this phenomenon is due to instability of the miRNAs, when unbound to AGO2 and/or GW182, or to the possibility that the miRNAs do not reach GW-bodies anymore, still needs to be elucidated.…”
Section: Transfer Of Ex-srnas Into Human Circulationmentioning
confidence: 99%
“…[105][106][107][108][109][110][111][112] miRNA sorting into exosomes can be influenced by a number of factors, 113 including dose, 114 3 0 end uridylation, 115 nucleotide sequence motifs, 116 interaction with RNA-binding proteins, 117,118 and localization to GW bodies. 119 Second, miRNAs can be incorporated into a variety of ribonucleoprotein complexes, including those containing ARGONAUTE family members, [120][121][122] HDL, 123,124 and HuR. 125 In addition, 2 other modes of sRNA spread that have been documented in vertebrates may play a role in invertebrates.…”
Section: Are Srnas Disseminated Systemically?mentioning
confidence: 99%